Lembar Kerja Berbasis Inkuiri untuk Pembelajaran Matematika Materi Segiempat Kelas VII MTs - Satiti, Wisnu Siwi; Virdella, Roziqul Lina; Hidayatulloh, Faisol (JoEMS (Journal of Education and Management Studies), 2023)
Students’understanding of mathematical concepts is important to be aquired, due to the use of mathematical concepts is variety of context in everyday life. One of the mathematical material that is widely used in real life is concept of Geometry: Quadrilaterals. However, based on the results of several previous studies and facts in the field, it shows that many students experience difficulties in the Quadrilaterals material. Therefore, in this study, teaching materials are developed to support learning. In this study, inquiry-based worksheets are developed on quadrilaterals for class VII students of SMP/MTs. This study is a development research by applying the ADDIE model. Based on the results of expert reviews, namely mathematics education lecturers and mathematics teachers, an average of 94% was obtained and meets the "Valid" criteria. LKPD obtained an assessment result of 88.46% which meets the "Practical" criteria. The results of implementing LKPD in learning obtained an average learning result of 83.5., of which 86.66% of students score above the KKM and only 13.34% of students score below the KKM. This shows that the use of inquiry-based worksheets can help students learn quadrilateral material.